Investigation of isotopes of ice in the Askinskaya and Kinderlinskaya caves (Southern Urals) - Ju. N. Chizhova; E. V. Trofimova; E. O. Dubinina; S. A. Kossova (Лëд и снег, 2023)
The aim of this work was to determine mechanisms of formation of perennial ice in caves of the Southern Urals, as well as to find sources of water and processes responsible for the formation of isotopic parameters of the cave ice. Isotopes δ18О and δD were investigated. The caves Askinskaya and Kinderlinskaya are the most famous ones in the Southern Urals located at the lowest levels a.s.l. (260 and 208 m, respectively). In the summer of 2019, samples of perennial ice and infiltration water were taken in both caves. Ices of the Askinskaya and Kinderlinskaya caves are characterized by a narrow range of δ18О and δD values with very slight variations in depth: −11.42…−12.89‰ and −83.8…−95.7‰, respectively. Values the isotopes in the infiltration water sampled in the Kinderlinskaya cave are: δ18О = −13 and δD = −76‰. For both Askinskaya and Kinderlinskaya caves, the isotopic parameters of ice correspond to the calculated line of Rayleigh crystallization in a closed system when water with the isotopes freezes. The narrow range of values δ18О and δD suggests that aufeises (naleds) existing in caves for many years are the congelation (hydrogenic) ice formed by the growth of thin water layers freezing through at a high rates. Infiltration waters are formed mainly due to the precipitation of the winter seasons. The ratio between winter and summer precipitation is about 2:1. The infiltration type of the cave ice alimentation as well as evidence of long time of averaging of the isotopic signal in the atmospheric precipitation do not allow to use the cave ices as a climatic (paleo)archive.